Radar Analysis Approach to Assess the Status of Hydromorphotectonic Changes in Central Iran(Yazd Ardakan Plain) - Sedigheh Emami; S.Ali Almodaresi; Mohamad Musaie sanjarehi (مخاطرات محیط طبیعی, 2020)
The phenomenon of the subsidence of the Earth is called the downward movement of the Earth's surface, which is not easily identifiable and quantifiable due to its slow evolution. The most appropriate method is to use radar data and differential interferometry techniques. Since physical compression and pressure drop are the main causes of subsidence in the places where water is extracted, D-InSAR's integrated zoning and its simultaneous investigation with subsurface factors reflect the anomalous deformation pattern created by subsurface factors. It shows well and demonstrates that the use of D-InSAR has been helpful in subsidence navigation. For this purpose, D InSAR radar data interferometry method was applied to ENVISAT and PALSAR radar satellite data from ASAR and ALOS sensors in 2006-2008, respectively. Ambient drought moderated the effect of phase change caused by atmospheric compounds, and the lack of challenge vegetation minimized the coherence of the phase radar images and made it possible to measure changes in the C and L band radar data annually. The maximum displacement was estimated by the C band of 0.14 m and by the L band of 0.12 m. Finally, we modeled the statistical results of the groundwater of the region and the amount of subsidence estimated by the mentioned radar images by linear regression method. There is groundwater, in relation to ASAR image per meter change in groundwater level we will have 0.025 meter change in ground level elevation and PALSAR (HH) image per meter change in groundwater level, 0.021 meter change in height we will have.